2021
DOI: 10.17660/ejhs.2021/86.1.10
|View full text |Cite
|
Sign up to set email alerts
|

Tree-adapted mechanical flower thinning prevents yield loss caused by over-thinning of trees with low flower set in apple

Abstract: yield and fruit quality in the production of apple fruit. thinning. In the years 2011, 2014-2016, commercial orchards of 'Elstar'/M26 and 'Gala'/M9 trained as set were mechanically thinned at balloon stage (BBCH 59) with the Darwin 250 device at constant vehicle speed of 8 km h -1 with varying rotational frequency ranging from 200 revolutions per minute (rpm) to 380 rpm. Rotational frequency of the thinning device was translated to average kinetic energy (E kin [J]) production target of 119 fruit and, therefor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 43 publications
0
5
0
Order By: Relevance
“…It appears that both systems could be used to manage the flower thinning with precision. For example, Penzel, et al [31] considered estimates of flower intensity as essential to manage mechanical flower thinning. In addition, these systems could be used to estimate the best timing to initiate the pollen tube growth model, developed by Yoder, Peck, Combs and Byers [16], and Peck, Combs, DeLong and Yoder [17].…”
Section: Discussionmentioning
confidence: 99%
“…It appears that both systems could be used to manage the flower thinning with precision. For example, Penzel, et al [31] considered estimates of flower intensity as essential to manage mechanical flower thinning. In addition, these systems could be used to estimate the best timing to initiate the pollen tube growth model, developed by Yoder, Peck, Combs and Byers [16], and Peck, Combs, DeLong and Yoder [17].…”
Section: Discussionmentioning
confidence: 99%
“…The estimation of FBC of each individual tree can be applied to develop VRAs of thinning. Mechanical VRA in thinning based on the flower set of the trees avoided over-thinning of each individual tree with a low flower set, which could increase the fruit yield by 1.4–7.6 t ha −1 (Penzel et al, 2021 ). Knowledge on the actual FBC of each individual tree may prevent overestimation and underestimation of thinning intensity and yield as confirmed in two commercial apple orchards earlier.…”
Section: Discussionmentioning
confidence: 99%
“…In fruit production, the number of apples per tree is negatively correlated to the mean fruit fresh mass (FM), coloration (Palmer et al, 1997), soluble solids content (SSC) (Link, 2000;Serra et al, 2016), and flower set in the following season (Handschack and Schmidt, 1991). Each individual apple tree may initiate up to 2,000 flowers, which significantly exceeds the commercially desired number of fruit at harvest (Penzel et al, 2021). Although a high percentage of flowers and later fruitlets will be naturally shed in flower or fruit abscission, often too many fruit remain on the tree.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Spatial variability in the trunk cross-sectional area, yield (Manfrini et al, 2020), fruit quality, canopy LA (Tsoulias et al, 2022), and the flower set (Penzel et al, 2021c) of individual fruit trees in commercial orchards have been described previously. Among the endogenous growth factors, it may be shown that both the small and large scale spatial variability of soil properties (Umali et al, 2012;Käthner et al, 2017) and terrain features can contribute to the inter-tree variability in yield and fruit quality.…”
Section: Introductionmentioning
confidence: 99%